2011
DOI: 10.1038/ijo.2011.163
|View full text |Cite
|
Sign up to set email alerts
|

Can we modulate physical activity in children?

Abstract: Intuition tells us that physical activity is central to weight reduction in obese children. Evidence, on the other hand, suggests that increases in physical activity are difficult to achieve in the short term, and may not be possible in the long term. One explanation could be an 'activitystat', a feedback loop in the child's brain that controls physical activity according to a set point. This brief article, which argues that it may not be possible to modulate the activity of children, reviews the principles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…For example, some studies have found that an increase in physical activity at one part of the day tends to be followed by a reduction in physical activity at another part of the day in children [47,48]. Conversely, some studies have shown no compensatory behaviour with children staying active after school, even if they were more active at school [31,32,49].…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies have found that an increase in physical activity at one part of the day tends to be followed by a reduction in physical activity at another part of the day in children [47,48]. Conversely, some studies have shown no compensatory behaviour with children staying active after school, even if they were more active at school [31,32,49].…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand, more than one third of young people aged 5-24 years are overweight or obese [6]. Because of its potential to increase daily energy expenditure, regular physical activity may be an important modifiable lifestyle behavior for both the prevention and treatment of childhood obesity [7,8], though the impact of physical activity on overall energy balance remains a topic of debate [9,10]. Furthermore, decreasing time spent being sedentary (engaging in sitting or lying activities associated with low levels of energy expenditure) has emerged as another potential target to promote energy balance and maintain optimal body composition.…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increasing interest in the activitystat concept of late and recent publications demonstrate that the issue is hotly contested in the physical activity research forum [4,5] . The number of published papers alone purporting to investigate the activitystat hypothesis is indicative of a growing trend in the literature.…”
Section: Introductionmentioning
confidence: 99%